Faktor - Faktor Yang Mempengaruhi Pemilihan Karir Akuntan Publik (Studi Kasus Mahasiswa Program Studi Akuntansi Fakultas Ekonomi dan Bisnis di Universitas Muhammadiyah Surakarta) - Utami, Novita; , Drs. Eko Sugiyanto, M.Si (2016)
The purpose of this study is to determine the effect of financial rewards, professional training, professional recognition, social values, work environment, labor market considerations for choosing their public accounting careers. The population in this study is the Student Accounting 2012 University of Muhammadiyah Surakarta force. The method of collecting the sample in this research is using convenience sampling technique. The sample was 82 respondents. In this study, to analyze the data was performed using logistic regression. The results showed that simultaneous variable financial rewards, professional training, professional recognition, social values, work environment , labor market considerations significantly influence career choice public accountants and non- accountants.